UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN DENGAN MENERAPAKAN MODEL DISCOVERY LEARNING DI SEKOLAH DASAR - Dea Mukti Nanjelita (Jurnal Basicedu, 2019)
The implementation of this research aims to improve mathematics learning outcomes of fractional material in fourth grade students of SDN Bandarjo 02 Ungaran by applying the Discovery Learning model.  In the learning process the steps of the Discovery Learning model are used, namely, stimulus, problem statements, data collection, data processing, verification, generalization.  The type of research used is classroom action research (CAR).  When observing mathematics learning, they have not used the right learning model for students.  Besides that from the data obtained 62.5% or 20 students is got grades was less than 66. The condition was considered bellow Minimum Passing Grade and 37.5% or 12 students had already reached Minimum Passing Grade.  The research lasted for 2 cycles where each cycle had 3 meetings.  After the first cycle of action, student learning outcomes increased 75% or as many as 24 Minimum Passing Grade students and 25% or 8 students did not reach Minimum Passing Grade.  In the second cycle of action student learning outcomes increased to 84.375% or 27 students who had reached Minimum Passing Grade and 15.625% or 5 students had reached those who had not yet reached Minimum Passing Grade.